2020
DOI: 10.1200/edbk_279901
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer in the Young: Epidemiology, Prevention, Management

Abstract: Colorectal cancer (CRC) incidence rates in the United States overall have declined since the mid-1980s because of changing patterns in risk factors (e.g., decreased smoking) and increases in screening. However, this progress is increasingly confined to older adults. CRC occurrence has been on the rise in patients younger than age 50, often referred to as early-onset disease, since the mid-1990s. Young patients are more often diagnosed at an advanced stage and with rectal disease than their older counterparts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
149
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(157 citation statements)
references
References 129 publications
(148 reference statements)
4
149
1
3
Order By: Relevance
“…Regarding genomic mutations, several studies have reported that early-onset SRCC is associated with a de novo deletion of CDH1, which encodes a protein functioning as an adherens junction; this to some extent explains why early-onset SRCC is more likely to be metastatic [15,20]. Regarding clinical characteristics, the distinct sex distribution between early-onset SRCC and late-onset SRCC may also account for the high malignancy [21]. In addition to distant metastasis, we found that lymphatic vessel invasion was more frequent in early-onset patients, which suggests that early-onset SRCC has greater malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding genomic mutations, several studies have reported that early-onset SRCC is associated with a de novo deletion of CDH1, which encodes a protein functioning as an adherens junction; this to some extent explains why early-onset SRCC is more likely to be metastatic [15,20]. Regarding clinical characteristics, the distinct sex distribution between early-onset SRCC and late-onset SRCC may also account for the high malignancy [21]. In addition to distant metastasis, we found that lymphatic vessel invasion was more frequent in early-onset patients, which suggests that early-onset SRCC has greater malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Early-onset non-polyposis CRC is a distinct entity with unique genetic features. Accumulating data suggest that early-onset CRC may have distinct clinicopathological features, including a more frequent occurrence in the rectum (32-57.7%), manifesting as mucinous (12.6%) or signet ring (10.8%) carcinoma and exhibiting poor differentiation features (20.4%) on histological analysis, and that diagnosis is mostly made at stages III and IV ( 8 , 21 23 ). All of these features were also determined in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that early-onset CRC has a more progressive biological behavior and a worse prognosis ( 6 , 35 ). This subset of patients has comparatively more concerns in a number of aspects, including the effects of treatment on fertility ( 8 ). These features raise a compelling concern as to the identification of prognostic markers and optimal treatment strategies, which may differ from the older-aged subset of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Tumor development, metastasis, and recurrence are the major contributors to CRC-related deaths; these processes are complex and largely unclear. 5,6 Unfortunately, approximately 25%-30% of patients are diagnosed at advanced stages mainly due to limited effective diagnostic techniques. 7 Accordingly, additional studies investigating CRC genesis and progression are of great significance for the identification of novel diagnostic and therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%